Answer:
Option C is the answer.
Explanation:
Given arithmetic series is 2.3 + 2.6 +2.9 + ......... 5 terms
Since this series is an arithmetic series so explicit formula of series will be
where a is the first term, d is the common difference and n is the number of term.
Therefore, we replace the values a = 2.3, and d = (2.6 - 2.3) = (0.3)
expression will be
![\sum_(n=1)^(n)[2.3+(n-1)(0.3)]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d2mdnabk3e0ewk3clnhtsrccihg52a0k7e.png)
![\sum_(n=1)^(n)[2.3+(0.3)n-0.3]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yff83cox0671y9224kfccnb1t1h8u0sdny.png)
![\sum_(n=1)^(n)[2+(0.3)n]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ffmcafr4plhqiuruoxerets2a1nyq9a7y9.png)
Option C is the answer.